2020
DOI: 10.1021/acs.jpcb.0c05657
|View full text |Cite
|
Sign up to set email alerts
|

Impregnation of Poly(methyl methacrylate) with Carbamazepine in Supercritical Carbon Dioxide: Molecular Dynamics Simulation

Abstract: Fully atomistic molecular dynamics simulations are employed to study impregnation of the poly­(methyl methacrylate) (PMMA) matrix with carbamazepine (CBZ) in supercritical carbon dioxide. The simulation box consists of 108 macromolecules of the polymer sample with the polymerization degree of 100, 57 molecules of CBZ, and 242,522 CO2 molecules. The simulation is performed at 333 K and 20 MPa. It is found that by the end of the simulation, the CBZ uptake reaches 1.09 wt % and 50 molecules are sorbed by PMMA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 71 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Examples of scCO 2 -assisted impregnation include the impregnation process for the dyeing of synthetic and natural textiles [28,29], preparation of drug-eluting implants [30][31][32][33][34][35][36][37], softwood processing [38][39][40][41][42][43], the preparation of hybrid silk material [44] or for food packaging applications [45,46]. In the conservation field, supercritical CO 2 technology is still niche, with a few examples of application such as the cleaning of textiles [47][48][49][50][51], deacidification of paper [52][53][54][55][56] and the removal of pesticides from objects in ethnographic collections [57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of scCO 2 -assisted impregnation include the impregnation process for the dyeing of synthetic and natural textiles [28,29], preparation of drug-eluting implants [30][31][32][33][34][35][36][37], softwood processing [38][39][40][41][42][43], the preparation of hybrid silk material [44] or for food packaging applications [45,46]. In the conservation field, supercritical CO 2 technology is still niche, with a few examples of application such as the cleaning of textiles [47][48][49][50][51], deacidification of paper [52][53][54][55][56] and the removal of pesticides from objects in ethnographic collections [57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Although the time and length scales of MD simulations are limited to a few nanoseconds and nanometers and significantly differ from experimental scale, MD is a useful and powerful tool for explaining phenomena observed in the experiment and at the same time for investigating systems at the molecular level. Previously, systems containing PMMA and scCO 2 were studied by MD [ 32 , 33 , 34 , 35 ], and it was shown that computer simulation allows obtaining molecular insight on swelling behavior of the polymer and obtaining tendencies sufficiently agreed with the ones observed in experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations can be conducted under high-temperature and high-pressure conditions . Equilibrium molecular dynamics, thermodynamic integration, Gibbs–Duhem integration, and Gibbs ensemble Monte Carlo (GEMC) can be used to investigate solubility and/or solubilization behavior by molecular simulations. We select GEMC in our investigation of solubility of hydrocarbons in CO 2 .…”
Section: Introductionmentioning
confidence: 99%